Children of heaven - Majid Majidi; Miramix International; Speedy Video Distribution Sdn. Bhd.; Institute for the Intellectual Development of Children & Young Adults ([Tehran, Iran] : Miramix International [publisher] ; Malaysia : Speedy Video Distribution Sdn. Bhd. [distributor], 1999)
When Ali loses his sister Zahra's school shoes, they dream up a plan to stay out of trouble: they'll share his shoes and keep it a secret from their parents
Title from title screen
Subtitles in English and Chinese
Acquisition for KPI (Kelab Pencinta Ilmu)
Editor, Hassan Hassandoost ; music, Keivan Jahanshani
Cast : Mohammad Amir Naji, Mir Farrokh Hashemian, Bahare Seddiqi
Keywords: Brothers and sisters -- Iran -- Tehran -- Drama; Shoes -- Drama; Tehran (Iran) -- Drama